PENGARUH DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM DENGAN DEVIDEND PAYOUT RATIO SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN BATUBARA DI BEI TAHUN 2021-2023 - Apriliana, Alhif (Jurnal Akuntansi AKTIVA, 2025)
Coal prices in 2023 have decreased. The supply chain problems that have begun to be resolved and the high interest rate policy have caused the demand side to be held back, causing coal prices to plummet. The recorded price of coal is 64.85%. Coal has a price of US$ 136.95 per ton at the end of 2023. Stock prices are formed from the supply and demand of a stock, if demand increasesAn increase in stock price typically signals a rise in investor confidence. On the other hand, when stock prices are elevated, it suggests growing trust from both current and potential investors in the company. This research aims to explore the connection between stock prices and the debt-to-equity ratio of firms listed on the Indonesia Stock Exchange between 2021 and 2023, with the dividend payout ratio acting as a moderating variable. Eleven samples representing a total of thirty-four businesses were analysed using SPSS 25.0 in this quantitative study. The results show that DER has a beneficial effect on stock prices, and that DPR helps to moderate this effect. These two findings are supported by the study's findings.